GIS Analysis of Solar PV Locations and Disaster Risk Areas in Japan - Hao, Kazuki; Ialnazov, Dimiter; Yamashiki, Yosuke (Frontiers in Sustainability, 2021)
Following the global trend of climate change mitigation, Japan has been rapidly increasing its share of renewable energy, in particular, its share of solar energy. However, Japan has limited flat land area that is suitable for solar photovoltaic (PV) power generation and a high risk of natural disasters. There is a possibility that some of its newly built solar power plants are located in areas where landslides and floods are likely to occur. Therefore, it is important to study the locations for solar PV from the perspective of disaster risk management. Previous studies have reported a number of incidents where solar PV installations were damaged as a result of natural disasters (Ohgami, 2019; Tabata, 2020). One study utilized geographical analysis technology to reveal the overlapping of solar PV powerplant locations and disaster-prone areas in Fukuoka prefecture in Japan (Kwon et at., 2020). However, to our best knowledge, no previous research about the solar PV locations’ hazard risks has been done on a national scale. This paper investigates the risks stemming from landslides and floods for the existing solar PV power plants in Japan. We compare the geographical data of disaster risks in Japan with the location data of solar PV power plants to investigate the number of solar PV power plants located in disaster risk areas. Our results show that the shares of medium and large-scale solar PV power plants located in areas where landslides and floods are likely to occur are about 8.5% and 9.1% respectively.